The effect of electricity consumption, price and coal exports on economic growth in South Africa - Chuene, Natasha Tlhologelo (My University, 2025)
Coal, recognized as a significant energy source, is a mineral commodity that is traded among countries. As a developing nation, South Africa is among the wealthiest and most dependent on coal as an input for electricity generation. Electricity consumption is a crucial contributor to GDP, and conversely, GDP plays a pivotal role in driving electricity consumption. However, the country faces a critical issue with electricity rationing and escalating electricity prices, sparking growing concerns as tons of coal are being exported. The study analyzed the effect of electricity consumption, electricity price, and coal exports on South Africa’s economic growth using quarterly data from 2016 to 2023. Through the Autoregressive Distributed Lag (ARDL), the study examined the long-run along with the short-run relationships. Secondly, to further inform policy, the Granger causality test was incorporated to evaluate the variables' causal relationship. Lastly, upon detecting existing causality, the economy's future path was forecasted through the Impulse Response Function (IRF) and Variance decomposition. In the long run, electricity consumption and price positively correlate with GDP at a 1% significance level, while coal exports negatively correlate with GDP at a 5% significance level. Electricity consumption aids productivity enabling seamless operations in various sectors. High electricity prices can drive businesses and households to invest in energy-efficient technologies and practices. This can lead to innovations and advancements in energy-saving solutions, fostering new industries and job creation. The export of coal in South Africa contradicts the export-led growth hypothesis as it has not resulted in significant economic benefits which is questionable due to the dire state of the country of having loadshedding. And as seen, load shedding has been detrimental to the economy. Thus, the findings of this study will provide policymakers with useful insights for making strategic decisions to enhance long-term economic growth and strengthen South Africa's energy sector.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2025
Keywords: GDP; ARDL; South Africa; Electricity consumption; Electricity price; Coal exports; Electric power -- South Africa; Electric power consumption -- South Africa; Gross domestic product -- South Africa; Coal trade -- South Africa; Economic development -- South Africa